ChemInform Abstract: CO2‐Tolerant and Cobalt‐Free SrFe0.8Nb0.2O3‐δ Perovskite Membrane for Oxygen Separation. Issue 24 (23rd May 2013) - Yi, Jianxin; Schroeder, Michael; Martin, Manfred
Abstract The title material is a promising candidate as oxygen permeable membrane for oxyfuel applications.